Combined effect of small molecule antiplasticizers and strain induced crystallization on properties of polyethylene terephthalate. Issue 3 (13th October 2018) - Zekriardehani, Shahab; Joshi, Anup S.; Jabarin, Saleh A.; Coleman, Maria R.
Abstract: In this work, the effect of strain‐induced crystallization (SIC) on blends of polyethylene terephthalate (PET) with antiplasticizers, dimethyl terephthalate, and dimethyl isophthalate has been studied. Both, inclusion of antiplasticizers and SIC affect the free volume, free volume distribution, and the barrier properties of PET. The addition of antiplasticizers and crystallization has a synergistic effect on the barrier properties and a twofold decrease in gas permeability relative to amorphous PET is observed. There is a shift in free volume and free volume distribution to smaller sizes combined with reduction in polymer segmental mobility that translates into a sharp decrease in diffusivity for all samples following SIC. While addition of antiplasticizers results in reductions in permeability, the formation of impermeable crystalline regions following SIC has the largest impact on overall permeability of the PET. Abstract : Inclusion of small molecule antiplasticizers and strain‐induced crystallization (SIC) synergistically affect the gas transport through polyethylene terephthalate. Due to the presence of impermeable crystalline regions upon stretching, contribution of the SIC process to the reduction in gas permeabilities overwhelms the effect of inclusion of antiplasticizers.